Analysis of Factors Influencing L1 Proficiency of Bilingual Children - Garcia, Leanne Margaret; Quinto, Edward Jay M.; Pacheco, Paula Enxi D. V.; Fallarme, Sophia Ysabelle R. (Technium Social Sciences Journal, 2024)
In the field of bilingualism, there are a multitude of studies that cover different topics such as the effects of early language exposure and the cognitive advantages of bilinguals, but one of the more underrepresented studies include the development of one’s first language, and the factors that play a part in it. In investigating the phenomenon of bilingualism, consideration on the intervening factors must be undertaken to create a more nuanced description of the relationship between the two variables. Hence, one-hundred Tagalog-English bilingual children aged 4-7 participated in the study to determine the difference of their L1 proficiency levels in terms of the following factors: (1) gender, (2) socio-economic status, (3) home language, and (4) community language. Participants were tasked to answer Tagalog proficiency tests covering grammar, vocabulary, and spelling to measure L1 proficiency. On the other hand, a demographic profile sheet was filled up by the parents to collect information on the factors provided. Analysis of variance (ANOVA) and the t-test was used to treat the data. The results showed the following: gender [F(1,98)=3.12; p=0.080] and socio-economic status [F(4,95)=0.93; p=0.448] were found to be insignificant to overall L1 proficiency, while those who reported using Tagalog as their home language [F(1,98)=11.04; p=0.001] and community language [F(1,98)=5.94; p=0.017] outperformed their English-using counterparts in L1 proficiency. The study ultimately displays that language exposure is a major element in the development of first language, and the interference of a second language may interrupt the proficiency of the first. However, the researchers recommend that future studies focus on specific factors and a thorough collection of data in order to accrue more accurate data.